Ignatius of Antioch: A Martyr Bishop and the Origin of Episcopacy. By Allen Brent - Hall, Stuart George (The journal of theological studies, 2008)
Allen Brent has produced a study of Ignatius that is learned, clear, and interesting, deserving the plaudits of scholars printed on its covers. His explanation of the importance of Ignatius in the past for establishing Anglicanism focuses on Ussher, and of the vindication of the seven letters of the ‘middle recension’ on Lightfoot. His reconstruction, from the only genuine evidence, the seven letters and the letter of Polycarp, of the career of Ignatius is full but concise and lucid. The consideration of the state of affairs at Antioch, where the chief trouble was internal disputes in the churches, is illuminating.